CONTENT AND LANGUAGE INTEGRATED LEARNING (CLIL) FOR ELT MATERIAL DEVELOPMENTS FOR BIOLOGY DEPARTMENT - St. Azisah; Ahmad Dai Zidan (International Conference on Social and Islamic Studies, 2021)
The Content and language integrated learning is learning a subject or part of a subject in a foreign language. So, students learn both of content knowledge and the foreign language. By CLIL, students learn English as foreign language integrated with the subjects or topics studied in department. This paper is aimed   to presents the material development for English language teaching for Biology Department with CLIL approach. The Rational for choosing this topic is based on the need for the students of Biology Department to learn the relevant English teaching materials with their field of study. The study is a qualitative study. Data were collected by using document analysis of curriculum of Biology Department as well as interviews with the lectures. Data then analyzed by using the framework of Miles and Huberman: data reduction, data presentation, conclusion/verification. The finding of this research that the CLIL materials needed for Biology Education Department included a number of topics of Biology studied in English.